Oral Propranolol and Prednisolone in the Treatment of Infantile Hemangioma: A Comparative Study (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Purpose: Infantile Hemangioma is a common vascular tumor of infancy and children. Although the lesions involute, the results are unpredictable and the time taken is variable. Responses to commonly used drugs like corticosteroid are not satisfactory due to variable effectiveness. There are also hazards of surgical intervention. The aim of this study is to compare the oral propranolol & prednisolone for IH treatment.Methods: In this study 104 patients were included. They were divided into 2 groups by systematic sampling method. In Group-A 52 patients were treated with oral propranolol and in Group-B 52 patients with oral prednisololne as per the protocol at a dose of 2mg/kg/day in two divided doses. Measurements of the size (directly measured by soft flexible rubber tape and calipers) and color assessment (image based by Adobe Photoshop software) were recorded before starting of the treatment. Follow up was done on 15th day, after 1st, 2nd, 3rd and 4th month respectively. Evaluation of percentage of regression of size and color clearance, adverse effects and treatment cost was done at each follow up. Regression in the size and color clearance of IHs was clinically assessed. Data were analyzed with the help of SPSS. P value of < .05 was considered significant.Results: In group-A 42(80.76%) had an excellent response, compared to group-B only 5(9.61%). In group-A, 40(76.92%) had an excellent color clearance, compared to group-B where only 03(05.76%). Regarding adverse effects in group-A, only 08 children (15.38%) complained of mild adverse effects which were self- limiting compared tothat of group-B (47,90.38%). In group-A average treatment cost was 165tk/ patient and in group-B 580tk. During follow up in group-A one case relapse was seen, in group-B 8 patient.Conclusion: Propranolol was safe, more effective and economic than oral prednisolone.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19414